Ice sheet model simulations reveal that polythermal ice conditions existed across the northeastern USA during the Last Glacial Maximum - J. K. Cuzzone; A. Barth; K. Barker; M. Morlighem (The Cryosphere)
Geologic archives of the Laurentide Ice Sheet (LIS) provide abundant constraints regarding the size and extent of the ice sheet during the Last Glacial Maximum (LGM) and throughout the deglaciation. Direct observations of LGM LIS thickness are non-existent, however, due to ice surface elevations likely exceeding those of even the tallest summits in the northeastern United States (NE USA). Geomorphic and isotopic data from mountains across the NE USA can inform basal conditions, including the presence of warm- or cold-based regimes, while covered by ice. While warm-based ice and erosive conditions likely existed on the flanks of these summits and throughout neighboring valleys, cosmogenic nuclide inheritance and frost-riven blockfields on summits suggest ineffective glacial erosion and cold-based ice conditions. Geologic reconstructions indicate that a complex erosional and thermal regime likely existed across the NE USA sometime during and after the LGM, although this has not been confirmed by ice sheet models. Instead, current ice sheet models simulate warm-based ice conditions across this region, with disagreement likely arising from the use of low-resolution meshes (e.g., > 20 km) which are unable to resolve the high bedrock relief across the NE USA that strongly influenced overall ice flow and the complex LIS thermal state. Here, we use a newer-generation ice sheet model, the Ice-sheet and Sea-level System Model (ISSM), to simulate the LGM conditions of the LIS across the NE USA and in three localities with high bedrock relief (Adirondack Mountains, White Mountains, and Mount Katahdin), with results confirming the existence of a complex thermal regime as interpreted from the geologic data. The model uses a small ensemble of LGM climate boundary conditions and a high-resolution horizontal mesh that resolves bedrock features down to 30 m to reconstruct LGM ice flow, ice thickness, and thermal conditions. These results indicate that, across the NE USA, polythermal conditions existed during the LGM. While the majority of this domain is simulated to be warm-based, cold-based ice persists where ice velocities are slow (< 15 m yr−1), particularly across regional ice divides (e.g., Adirondack Mountains). Additionally, sharp thermal boundaries are simulated where cold-based ice across high-elevation summits (White Mountains and Mount Katahdin) flanks warm-based ice in adjacent valleys. We find that the elevation of this simulated thermal boundary ranges between 800–1500 m, largely supporting geologic interpretations that polythermal ice conditions existed across the NE USA during the LGM; however, this boundary varies geographically. In general, we show that a model using a finer spatial resolution compared to older models can simulate the polythermal conditions captured in the geologic data, with the model output being of potential utility for site selection in future geologic studies and for geomorphic interpretations of landscape evolution.